INCREASING THE ENGLISH VOCABULARY OF MEDICAL STUDENTS THROUGH BLENDED LEARNING BASED ON THE MOODLE LMS PLATFORM - Jonzaqova Nigora Nizamiddin qizi (Prospects for innovative technologies in science and education, 2025)
This study investigates the effectiveness of blended learning based on the Moodle Learning Management System (LMS) in developing the English lexical competence of medical students. In the context of the growing role of English as the primary language of medical science and professional communication, the improvement of medical students’ vocabulary acquisition has become a priority in higher medical education in Uzbekistan. The research analyzes the didactic potential of the Moodle platform, develops interactive learning modules for medical English, and implements synchronous and asynchronous learning activities within a blended learning model. An experimental study was conducted among second-year medical students, divided into experimental and control groups. The results of pre-tests and post-tests demonstrated that students in the experimental group achieved significantly higher vocabulary development (by 23–28%) compared to those taught through traditional methods. The findings confirm that Moodle-based blended learning enhances students’ motivation, independent learning skills, and professional language competence. The results of the study can be effectively applied in modernizing foreign language education in higher medical institutions.